THE INFLUENCE OF LOCAL GOVERNMENT SUPPORT ON SMES PERFORMANCE IN INDONESIA (Lex localis - Journal of Local Self-Government, 2025)
The objective of this study is to investigate of government support on the performance of SMEs. The Resource-Based View (RBV) is a theoretical framework used in strategic management to analyze how a company’s internal resources and capabilities can become sources of sustainable competitive advantage. Government support for the performance of Micro, Small, and Medium Enterprises (SMEs) in Indonesia is crucial, especially in the context of post-pandemic economic recovery and strengthening competitiveness. The methodology adopted this study is explanatory research aimed at analyzing the impact of government support on the performance of micro, small, and medium enterprises (SMEs) in North Sumatra. The type of data used is primary data, collected through the distribution of questionnaires to 221 respondents. The analysis includes testing research instruments (inner model and outer model) and hypothesis testing (bootstrapping test), using Structural Equation Modeling (SEM) as the model.The findings of the study demonstrate that government support in terms of policy, financing, mentoring, and social programs significantly affects SMEs performance. Government support is crucial for the performance of SMEs in Indonesia, as it fosters business growth, which in turn enhances SME performance. Through these initiatives, local governments aim to improve SME competitiveness, strengthen the local economy, and create sustainable job opportunities. Such support is vital for SMEs to develop, compete, and make a greater contribution to the national economy. The implications of this research highlight the importance of government support in improving SME performance. While access limitations are generally within reasonable bounds given the capacity of each SME owner, effective business development and growth in the SME sector require substantial support. Running a business also necessitates aspects such as regulation, financing, mentoring, and social programs.